The successful factor for Atmalink Sdn Bhd to create a high quality of training services for local and foreign market / Mohd Roslaidi Mohamad - Mohamad, Mohd Roslaidi (Faculty of Business and Management, 2010)
According to the topic chosen, The Successful Factor for Atmalink Sdn Bhd to Create a High Quality of Training Services for Local and Foreign Market, the research is conducted to find the result for the finding. Research objectives for this study undertaken are To identify whether the promotion done is well enough to create a high quality of training service, to determine whether the level of the quality training program can be measured by the price offered, to identify whether product/service offered may influence the quality of training program and To determine whether place are also effect the level of the quality training program. The scope of the study is mainly focusing on the factors, which is promotion, price, product/service, and place and its effect to the quality of the training program. A set of questionnaires was distributed to the respective respondents. Several factors that being discussed in this research are demographic, 4Ps elements that contributes to the quality of the training program. The data is analyzed using descriptive analysis, frequency, reliability testing and Pearson correlation of Statistical Package for Social Sciences (SPSS).